Determination of total phenolics, flavonoids, and testing of antioxidant and antibacterial activities of red ginger (Zingiber officinale var. Rubrum) - Haroen, Ucop; Syafwan, Syafwan; Kurniawan, Kiki; Budiansyah, Agus (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The purpose of this study was to select the active fraction of red ginger (Zingiber officinale var. Rubrum) for its antioxidant and antibacterial activities against Staphylococcus aureus (AMC 6934), Bacillus subtilis (AMC 7923), Pseudomonas aeruginosa (AMC 8973), and Escherichia coli (AMC 5761). Materials and Methods: A total of 2 kg of dry red ginger rhizome powder was macerated in stages with different levels of solvent polarity to extract the chemical composition within the red ginger powder sample. The extraction process begins with a non-polar solvent (n-hexane) by soaking the red ginger powder sample for 3 × 24 h. Results: The red ginger extract fractionated with methanol produced alkaloids, phenolics, flavonoids, and coumarins, while the fractionation using n-hexane produced alkaloids and triterpenoids only. The fractionation with ethyl acetate produced alkaloids, phenolics, flavonoids, triterpenoids, saponins, and coumarins. The antioxidant activity test was 49.261 mg/l for the ethyl acetate fraction, 146.648 mg/l for the methanol fraction, and 300.865 mg/l for the n-hexane fraction. Conclusion: The ethyl acetate fraction was effectively powerful in inhibiting the growth of Grampositive and Gram-negative bacteria. All fractions had moderate antibacterial activity; however, the performance of ethyl acetate in the red ginger extract was better than that of methanol and n-hexane. Adv. Vet. Anim. Res., 11(1): 114-124, March 2024 http://doi.org/10.5455/javar.2024.k755